The first-past-the-post electoral system versus proportional representation in Africa : a comparative analysis - Comoane, Paulo (University of Pretoria, 2012)
Prepared under the supervision of Mr Paulo Comoane at the Faculty of Law, Eduardo Mondlane University, Mozambique